Structural studies on orbivirus proteins and particles. - Stuart, D; Grimes, J (2006)
X-ray and electron microscopy analysis of Bluetongue virus (BTV), the type species of the Orbivirus genus within the family Reoviridae, have revealed various aspects of the organisation and structure of the proteins that form the viral capsid. Orbiviruses have a segmented dsRNA genome, which imposes constraints on their structure and life cycle. The atomic structure of the BTV core particle, the key viral component which transcribes the viral mRNA within the cell cytoplasm, revealed the architecture and assembly of the major core proteins VP7 and VP3. In addition, these studies formed the basis for a plausible model for the organisation of the dsRNA viral genome and the arrangement of the viral transcriptase complex (composed of the RNA-dependent RNA polymerase, the viral capping enzyme and RNA helicase) that resides within the core particle. Electron cryo-microscopy of the viral particle has shown how the two viral proteins VP2 and VP5 are arranged to form the outer capsid, with distinct packing arrangements between them and the core protein VP7. By comparison of the outer capsid proteins of orbiviruses with those of other nonturreted members of the family Reoviridae, we are able to propose a more detailed model of these structures and possible mechanisms for cell entry. Further structural results are also discussed including the atomic structure of an N-terminal domain of nonstructural protein NS2, a protein involved in virus genome assembly and morphogenesis.